Impacts of Changes in Atmospheric O2 on Human Physiology. Is There a Basis for Concern? - Keeling, Ralph F.; Powell, Frank L.; Shaffer, Gary; Robbins, Peter A.; Simonson, Tatum S. (Frontiers in Physiology, 2021)
Concern is often voiced over the ongoing loss of atmospheric O2. This loss, which is caused by fossil-fuel burning but also influenced by other processes, is likely to continue at least for the next few centuries. We argue that this loss is quite well understood, and the eventual decrease is bounded by the fossil-fuel resource base. Because the atmospheric O2 reservoir is so large, the predicted relative drop in O2 is very small even for extreme scenarios of future fossil-fuel usage which produce increases in atmospheric CO2 sufficient to cause catastrophic climate changes. At sea level, the ultimate drop in oxygen partial pressure will be less than 2.5 mm Hg out of a baseline of 159 mmHg. The drop by year 2300 is likely to be between 0.5 and 1.3 mmHg. The implications for normal human health is negligible because respiratory O2 consumption in healthy individuals is only weakly dependent on ambient partial pressure, especially at sea level. The impacts on top athlete performance, on disease, on reproduction, and on cognition, will also be very small. For people living at higher elevations, the implications of this loss will be even smaller, because of a counteracting increase in barometric pressure at higher elevations due to global warming.